A Computational Method for Dynamic Analysis of Deployable Structures - Ying Wang; Bin Sun (Shock and Vibration)
A computational method is developed to study the dynamics of lightweight deployable structures during the motion process without regard to damping. Theory and implementation strategy of the developed method are given in this study. As a case study, the motion process of a bar-joint structure and a ring array scissor-type structure was simulated under external dynamic loading. In order to verify the effectiveness of the method, the simulation results are compared with the results predicted by the authenticated multibody system dynamics and simulation program. It shows that the method is effective to dynamic analysis of deployable structures no matter the structures are rigid or elastic. Displacement, velocity, and acceleration for the entire deployable structures during the motion process can be computed, as well as strain if the deployable structure is elastic.